Investigating the Benefits of Multimodal Project-Based Learning in Teaching English to International Students - Mohamed, Amr M. (International Journal of Educational Innovation and Research, 2023)
This research investigates how English as a Foreign Language (EFL) educators in Saudi Arabian higher education institutions modify their approach to implement project-based learning (PJBL) in their classrooms. Eleven EFL teachers with experience in PJBL implementation were selected for email interviews, and the data were analyzed using thematic analysis. The data was procured by means of email interviews conducted with the participants, wherein the interview questions were formulated based on the research inquiries and encompassed various dimensions of PjBL implementation in EFL instruction. The participants were instructed to furnish their responses to the questions via email, and subsequently, their replies were meticulously transcribed verbatim. The results showed that the teachers employed various adaptation strategies, including modifying the project tasks to suit the language level of the students, using scaffolding techniques to support learning, and incorporating multimodal elements into the projects. The study highlights the importance of teacher autonomy and flexibility in adapting PJBL to the needs of EFL learners. The findings also suggest that PJBL has the potential to enhance language learning and promote critical thinking skills. However, some limitations to PJBL implementation were identified, such as the need for additional training and resources. The study provides recommendations for EFL teachers and institutions to improve PJBL implementation and support effective language learning.